(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the impact of the Covid-19 pandemic on leprosy care from the perspective of health professionals. This is a descriptive, cross-sectional, service evaluation study using a printed questionnaire, aimed at medical health professionals, nurses and physiotherapists. The study was carried out with 17 health professionals, 7 nurses, 7 physicians and 3 physiotherapists belonging to 7 primary care health units in a municipality in Pará. It was observed that only 24% of the professionals interviewed underwent sector relocation, 82% of professionals said that there were changes in the service profile of the health units, there was a need to reschedule care for patients, 88% of professionals underwent rotation of activities, 47% said there was a lack of medication for the treatment of leprosy in the units where they work, 53% said there was no lack of materials for the care of leprosy patients, there were difficulties in scheduling laboratory tests, in the evaluation of home and social contacts and in the referral and counter-referral of patients. From these data, it is concluded that the Covid-19 pandemic created difficulties for the care and treatment of patients with leprosy in participating primary health care units, causing delays in appointments, rescheduling of appointments, extensions of treatment due to lack of medication, difficulties in evaluating contacts and active search for new cases, contributing to generate a negative impact on the program and consequently on the health system.